Self-Management of Work in the Creative Industries in the Netherlands - Hennekam, S.; Bennett, Dawn (ECOLE DES HAUTES ETUDES COMMERCIALES DE MONTREAL, 2016)
A paucity of research on the characteristics of creative work in the Netherlands means that decision-making is inhibited by a reliance on datasets with insufficient resolution for finer analysis to be undertaken. It is likely that the most vulnerable creative workers – those whose work is sporadic and features multiple concurrent roles – are the least represented in official data collections. The study we report here draws on an in-depth survey of the portfolios of work as reported by 511 individual creative workers, the paper highlights the complexity of creative work. The results and implications centred on four key themes: multiple roles; multiple identities; an unstable income; and career. In the light of the increasing self-employment in the creative industries and the related challenges, we stress the precarious nature of creative careers and the vulnerability of creative workers. Implications for management and recommendations to deal with these issues are discussed.